Coupled Effects of Surface-Radiation and Buoyancy on Jet-Impingement Heat Transfer - Abishek, S.; Narayanaswamy, Ramesh (American Society of Mechanical Engineers, 2012)
This paper delineates the results of an investigation on the combined effects of buoyancy and surface-radiation on heat transfer from an isothermal surface, subjected to a confined submerged impinging air-jet issuing from a slot-nozzle. The nondimensionalized governing equations are solved using the stream function-vorticity approach and an upwind finite-difference technique, employing the radiosity-irradiation formulation for surface-radiation. The effects of jet Reynolds number, dimensionless nozzle-to-heater distance, radiation-flow interaction parameter, Richardson number, and surface-emissivity, on the convective, radiative, and total Nusselt numbers, are analyzed for 100 ≤ Re d ≤ 900, 1 ≤ H ≤ 8, 0.1 ≤ NRF,d ≤ 2, 0.01 ≤ Ri d ≤ 10, and 0.05 ≤ Ɛ 0.85. It was found that the radiation-flow interaction parameter was most influential in affecting the radiative Nusselt number and, hence, the total heat transfer from the impingement surface. In contrast to a substantial enhancement in the net radiative component of the overall heat transfer in both the stagnation region and the regions downstream for an increase in Ɛ over the range considered, the convective counterpart was found to be suppressed. The effect of increase in Rid on the heat transfer in the stagnation region was found to be negligible; however, an adverse effect on the net radiation from the heater was observed.Increase in NRF,d resulted in an increase in contribution of radiation to the total heat transfer by about 25% in the stagnation region, while over 40% in the wall-jet region for low values of H, and to about 15% in the stagnation region to over 50% in the wall-jet region for relatively larger values of H. With increase in H, both convective and radiative Nusselt numbers decreased over most of the upstream regions of the heater, while the magnitude of local radiative Nusselt numbers increased over the regions closer to the outlet. For sufficiently large values of jet Reynolds number or large values of dimensionless nozzle-to-heater distance, a small recirculation region was found to occur over the heater at a certain distance downstream of the stagnation point, where distribution of the contribution of radiation to the overall heat transfer from the heater results in a local maxima reaching about 60–80% for specific combinations of controlling parameters.